Implementasi Jurnalisme Damai pada Konflik PT KAI dan Warga Anyer Dalam di Media Daring - Ardiansyah, Syifa Maulidha; Sumadiria, AS Haris; Astuti, Dyah Rahmi (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This paper aims to explain of four peace orientations, namely peace orientation, truth orientation, community orientation, and settlement orientation. This study uses the concept of peace that was coined by Johan Galtung. The research method used is descriptive method with data collection techniques through passive participatory observation and interviews. The results of the study show that the peace orientation includes elements of balance, cause and effect, and views conflict through various perspectives. Truth orientation is the basic ethos of the press, by transforming reality into writing, as well as revealing the untruth that exists in the conflict. Community orientation focuses on the losses suffered by voiceless parties, as well as raising the names of criminals and parties who promote peace. The orientation of the settlement is sought to achieve resolution, reconstruction, and reconciliation of conflicts.